The The effects of the SPARK program on physical activity engagement in 11-year-old children - SITI AISHAH ABD RAHMAN; Nurul Diyana Sanuddin; Norlaila Azura Kosni; Nurshahira Ibrahim; Adjullea James @ Noew; Asmalini Che Abu Shafie; Theresa Ahing; Gordon Nicolaus Jemat Anchang; Mohamed Azizul Mohamed Afandi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The SPARK (Sports Play Active and Recreation for Kids) program is a holistic health initiative with the primary goal of enhancing moderate to vigorous physical activity (PA) in children, focusing on improving physical fitness, fostering sports skills, and contributing to academic achievements. The main purpose of this study was to see the effectiveness of the SPARK program on interest in physical activity among 11-year-old children. This SPARK program contains four physical and four skill fitness activities that will be applied for eight (8) weeks in four selected primary schools in Perak. This study is a quasi-experimental pre and post-control group design. 240 children consisting of boys and girls were selected as a study sample. The selection of participants is based on the 'intact sampling' method, in a situation where all students in fifth grade (5) classes are retained as study subjects, consisting of 120 students in the treatment group and 120 students in the control group. Two-way ANCOVA analysis shows a significant difference in mean post-score for interest in physical activity between the treatment groups for male and female students by controlling the pre-score after undergoing the SPARK Program. The SPARK program provided positive and significant changes to the children who received the program intervention compared to those who attended Physical Education classes as usual. The implications of the study show that the use of the SPARK program attracts children to participate in physical activities and can subsequently increase the level of physical fitness performance among children.